Diseño, estructuración y operacionalización de un sistema de autogestión para el centro de desarrollo integral El Niño, ubicado en Amaguaña - Díaz Cumba, María Eugenia (2006)
With the information presented above, we start to design and structure and operationalize a self, allowing the sustainability of the institution providing services for children with disabilities with limited economic resources, in order to improve quality of life, through actions involving children, family, and the community at large, to put emphasis on the issue of physical and intellectual disabilities, considering their needs for decision-making and institutional strengthening strategies.